Associations of Blood Lipids with the Risk and Prognosis of Sudden Sensorineural Hearing Loss: A Meta-analysis - Jie Li; Yong-Ming Zhu; Ya-Qin Wang; Xiao-Chun Gu (Journal of International Advanced Otology)
Bacground: Patients with sudden sensorineural hearing loss (SSNHL) may lose their hearing. The relationship between SSNHL and total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) levels is still unclear. The association of TC, TG, HDL-C, and LDL-C levels with the risk and prognosis of SSNHL was explored in this study.